2018
DOI: 10.1016/j.ijid.2018.04.794
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antimicrobial resistance of pathogens in neonatal septicemia in China—A meta-analysis

Abstract: It is concluded that Staphylococcus, especially coagulase-negative Staphylococcus, continues to be the principal organism responsible for neonatal septicemia in China; Enterobacteriaceae are common among the Gram-negative isolates. Significant numbers of MRSA and multidrug-resistant Gram-negative bacteria are being isolated as pathogens responsible for neonatal septicemia in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 37 publications
7
37
1
Order By: Relevance
“…Moreover in consistent with our findings, results from another large systematic review indicated that Enterobacter species, Klebsiella, Escherichia coli, Pseudomonas species, and Streptococcus pneumonia were recognized as the most common bacterial pathogens of neonatal sepsis in the Middle East region [52]. In a country-level meta-analysis in China, Li et al reported that Staphylococcus, Enterococcus, Escherichia, and Klebsiella were found to be the most common organisms responsible for neonatal septicaemia in China [53]. This variation could also be explained by differences in geographical and climatic parameters in different regions.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover in consistent with our findings, results from another large systematic review indicated that Enterobacter species, Klebsiella, Escherichia coli, Pseudomonas species, and Streptococcus pneumonia were recognized as the most common bacterial pathogens of neonatal sepsis in the Middle East region [52]. In a country-level meta-analysis in China, Li et al reported that Staphylococcus, Enterococcus, Escherichia, and Klebsiella were found to be the most common organisms responsible for neonatal septicaemia in China [53]. This variation could also be explained by differences in geographical and climatic parameters in different regions.…”
Section: Discussionsupporting
confidence: 91%
“…The MDR patterns in both Gram-negative and Gram-positive bacteria in our study (84.4%) is by far higher than national and global reports: Ethiopia (65%) [26], Jordan (69%) [23], and China (50%) [40].…”
Section: Discussioncontrasting
confidence: 69%
“…Concerning to drug resistance, the isolates in the present study were resistant against commonly used antibiotics in the area and high frequency of MDR bacterial pathogens were observed predominantly among the Gram-negative bacteria. Recent studies in Ethiopia, India, Nepal, and China also showed high levels of resistance in Gram-negative organisms against ampicillin (85%, 78%, 100%, 80%), respectively, and ceftriaxone (57%, 100%, 100%, 50%), respectively [26,29,30,40].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, one-third were caused by gram negative bacilli and 70 (18.6%) were multidrug resistant [17]. A meta-analysis of 71 studies reported from China showed that 50% of gram negative organisms were resistant to thirdgeneration cephalosporins [18].…”
Section: Multidrug Resistance: Global Picturementioning
confidence: 99%